Awareness of Postpolypectomy Surveillance Guidelines: A Nationwide Survey of Colonoscopists in Canada - Harmke van Kooten; Vincent de Jonge; Eline Schreuders; Jerome Sint Nicolaas; Monique E van Leerdam; Ernst J Kuipers; Sander JO Veldhuyzen van Zanten (Canadian Journal of Gastroenterology)
Several studies have demonstrated that screening asymptomatic, average-risk individuals and those at increased risk can reduce colorectal cancer mortality. Adherence to postpolypectomy surveillance guidelines becomes increasingly important amid the increasing demands for colonoscopy because suboptimal compliance can lead to unnecessary risks and the ineffective use of resources. However, performing too many surveillance colonoscopies, or at intervals that are too short, may hinder access to endoscopic procedures and decrease the cost effectiveness of colorectal cancer screening programs. Two reasons appear to be primarily responsible for nonadherence to postpolypectomy guidelines: lack of awareness or familiarity, and disagreement with the guidelines. Accordingly, this study aimed to determine the awareness of postpolypectomy guidelines among members of the Canadian Association of Gastroenterology, and the factors associated with physicians’ choices to deviate from them.